The Effectiveness of Short-Term Object Relations Therapy on the Dimensions of Shame in Women with Multiple Sclerosis (MS): A Randomized Clinical Trial - Mesghali , Ghazal; Talebi, Gholamreza; Oreyzi, Hamidreza (Psychology of Woman Journal, 2026)
Objective: The present study aimed to determine the effectiveness of short-term object relations therapy on the dimensions of shame in women with multiple sclerosis. Methods and Materials: This study was an applied quantitative research conducted using a quasi-experimental design with pretest, posttest, and three-month follow-up, including an experimental group and a control group. The statistical population consisted of women diagnosed with multiple sclerosis referred to medical centers in Isfahan during 2025–2026. A total of 36 participants were selected through convenience sampling and randomly assigned to an experimental group (n = 18) and a control group (n = 18). The experimental group received short-term object relations therapy based on Masterson’s protocol in 14 sessions (45 minutes each, twice weekly), while the control group received no intervention. Data were collected using the Experience of Shame Scale (ESS), which assesses characterological, behavioral, and bodily shame. Data analysis was performed using SPSS-29 at both descriptive and inferential levels, including repeated-measures analysis of variance and Bonferroni post hoc tests. Findings: The results of repeated-measures ANOVA indicated significant effects of time, group, and the interaction between time and group on total shame and all its dimensions (p < 0.001), with large effect sizes. Bonferroni post hoc tests showed that shame scores in the experimental group significantly decreased from pretest to posttest and from pretest to follow-up (p < 0.001), while no significant differences were observed between posttest and follow-up stages, indicating stability of treatment effects. No significant changes were observed in the control group. Conclusion: Short-term object relations therapy is an effective intervention for reducing the dimensions of shame in women with multiple sclerosis, and its effects are stable over time, suggesting its potential as a valuable psychotherapeutic approach for improving emotional functioning in this population.